Novel redox-active enzymes for ligninolytic applications revealed from multiomics analyses of Peniophora sp. CBMAI 1063, a laccase hyper-producer strain - Brenelli, Lívia B.; Persinoti, Gabriela F.; Cairo, João Paulo L. Franco; Liberato, Marcelo V.; Gonçalves, Thiago Augusto; Otero, Igor V. R. [UNESP]; Mainardi, Pedro H. [UNESP]; Felby, Claus; Sette, Lara D. [UNESP]; Squina, Fabio M. (Springer Nature, 2019)
The repertoire of redox-active enzymes produced by the marine fungus Peniophora sp. CBMAI 1063, a laccase hyper-producer strain, was characterized by omics analyses. The genome revealed 309 Carbohydrate-Active Enzymes (CAZymes) genes, including 48 predicted genes related to the modification and degradation of lignin, whith 303 being transcribed under cultivation in optimized saline conditions for laccase production. The secretome confirmed that the fungus can produce a versatile ligninolytic enzyme cocktail. It secretes 56 CAZymes, including 11 oxidative enzymes classified as members of auxiliary activity families (AAs), comprising two laccases, Pnh_Lac1 and Pnh_Lac2, the first is the major secretory protein of the fungi. The Pnh_Lac1-mediator system was able to promote the depolymerization of lignin fragments and polymeric lignin removal from pretreated sugarcane bagasse, confirming viability of this fungus enzymatic system for lignocellulose-based bioproducts applications.